2007
DOI: 10.3748/wjg.v13.i6.930
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole-based triple therapy with low-versus high-dose of clarithromycin plus amoxicillin forH pylorieradication in Iranian population

Abstract: AIM:To investigate the efficacy and tolerability of H pylori eradication in an omeprazole-based triple therapy with high-and low-dose of clarithromycin and amoxicillin. C-urea breath test 6 wk after the therapy. Standard questionnaires were administered to determine the compliance to treatment and possible adverse events of therapy. Data were subject to χ 2 to compare the eradication rates in the two groups. The significant level of 95% (P ≤ 0.05) was considered statistically different. METHODS: RESULTS:We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In addition, a multicenter study conducted in France showed a higher, although not significant, eradication rate with low-dose clarithromycin triple therapy compared with the conventional regimen [22]. A recent study from Iran [19] evaluating a low-dose versus high-dose of omeprazolebased triple therapy in combination with amoxicillin and clarithromycin also demonstrated that the low-dose regimen was as effective as the high-dose regimen, with ITT eradication rates of 85 and 83.8%, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, a multicenter study conducted in France showed a higher, although not significant, eradication rate with low-dose clarithromycin triple therapy compared with the conventional regimen [22]. A recent study from Iran [19] evaluating a low-dose versus high-dose of omeprazolebased triple therapy in combination with amoxicillin and clarithromycin also demonstrated that the low-dose regimen was as effective as the high-dose regimen, with ITT eradication rates of 85 and 83.8%, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…As observed in our trials, no homogeneous trend was prevalent among the different studies, as some studies’ results favoured full‐dose regimens while others favoured half‐dose therapies. In some cases, inconsistent results were obtained from the same study, as the PP and ITT analyses yielded contradicting conclusions . Despite that fact, most of the results showed statistical insignificance and for that reason, heterogeneity among studies was assessed and found to be 37% ( I 2 = 37%), which is a considerable value in the light of the chi‐squared statistic P ‐value of 0.05, most likely due to the different treatment regimens and durations used in the selected studies (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…repeated the analysis after including one additional RCT of 352 patients and found no significant difference in the 500 mg dose of clarithromycin in amoxicillin‐containing triple regimen . As a large number of additional studies have addressed this question, the evidence from these individual trials suggests that half‐dose clarithromycin may be equally effective to standard full‐dose therapy, but is associated with less costs and side effects . In this systemic review and meta‐analysis, we review all the studies published to date with the aim of assessing the safety and efficacy of half‐dose vs. full‐dose clarithromycinin H. pylori treatment.…”
Section: Introductionmentioning
confidence: 99%
“…To date, three randomized controlled trials, involving a total of 475 patients, have examined the value of 50% reduction in the dose of all administered antibiotics for H. pylori (two STT and the current concomitant NBQT) and have all confirmed similar eradication rates to the standard-dose comparator (Table 4), with a reduction in adverse events and cost. 13,33 This concept is attractive and challenges the prevailing dogma in the treatment of H. pylori. One theoretical concern, however, is that these low-dose regimens may produce prolonged sub-minimum inhibitory concentration effects which may, in turn, contribute to development of resistant strains.…”
Section: Discussionmentioning
confidence: 99%